A review of metal-organic frameworks (MOFs) as energy-efficient desiccants for adsorption driven heat-transformation applications. (1st July 2020) - Karmakar, Avishek; Prabakaran, Vivekh; Zhao, Dan; Chua, Kian Jon
Highlights: One-stop archive for recent developments in water-sorbing MOFs. Key factors essential for synthesizing stable MOFs are reviewed comprehensively. Advantages of MOFs over conventional pure and composite desiccants are discussed. Thorough analysis on the integration of MOFs with heat transformation applications. Potential in energy storage and water harvesting applications are highlighted. Abstract: Energy-efficient alternative cooling technologies are necessary to reduce the sharp rise in building energy requirements. The currently employed vapor compression air-conditioners are non-environmentally friendly and exhibit low efficiency due to the concurrent handling of sensible and latent cooling loads. Adsorption chillers and desiccant dehumidifiers are promising alternatives that can trim the overall carbon footprint. Their cooling energy efficiency is dependent on the adsorption characteristics of the employed desiccants. Conventional desiccants suffer from low equilibrium capacity, slow adsorption-desorption dynamics, the needs for high regeneration temperatures, and the lack of hydrothermal and cyclic stabilities. With excellent hydrophilicity, exceptional structural integrity, and specific host-guest interactions, metal-organic frameworks (MOFs) are deemed to be the next generation of advanced materials with tailorable structures for specific applications. In this review article, we focus on the recent developments in MOFs and their potential employment in several state-of-the-art applications such as heat transformation, energy storage, and water harvesting. The advantages of MOFs over conventional pure and composite desiccant materials are discussed, and the key factors necessary for synthesizing stable MOFs are reviewed comprehensively. The experimental and computational characterization techniques employed to investigate the properties of MOFs are studied. Lastly, factors that are essential to screen MOFs for specific applications are analyzed, and key research gaps and technological advancements pertaining to material development and engineering demands are also highlighted. In sum, this review article offers an extensive update on the latest trends in water-sorbing MOFs and is intended to serve as a one-stop archive for its potential applicability.